Hubungan Pengetahuan terhadap Perilaku Penggunaan Obat Kumur di Bulan Ramadhan - Sabiti, Farroh Bintang; Rochajati, Siti; Haq, Mailatul Ilal (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: One of the health problems that often occur during the fasting month is problems with the teeth and mouth. Dental and oral problems are important things to pay attention to. Apart from causing bad breath, this can also affect a person's self-confidence. Generally, dental and oral problems can be prevented by using mouthwash. When using mouthwash during the Ramadhan, it must be done properly and correctly. Good knowledge towards the practice of using mouthwash is very important. Methods: This research is a descriptive study with a cross sectional approach used random sampling techniques. Data analysis used the Spearman test. Results: The category of knowledge of mouthwash medicines at Semarang city health center was 83% in the good category. Meanwhile, in the practice category, 80% were in the good category and 20% were in the bad category. Conclusion: There is a relationship between knowledge and public attitudes regarding the practice of selecting halal herbal medicines in pharmacies. Where the significant values are between knowledge and practice using mouthwash at ramadhan (0.00*),